Urgensi Penguatan Kedudukan Dispute Board guna Menjamin Kepastian Hukum Proyek Jalan Multi-Tahun - Paksi Aan Syuryadi; Muhtadi Muhtadi; Kasmawati Kasmawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
Multi-year infrastructure projects are inherently characterized by high legal and financial complexities, where conventional litigation and post-project arbitration often prove to be protracted, reactive, and deleterious to project continuity. While the Indonesian regulatory framework, specifically Government Regulation No. 22 of 2020, has formally recognized the Dispute Board (DB) mechanism, its practical efficacy remains constrained by a profound normative lacuna regarding executorial enforceability. This research employs a legal-doctrinal method with a comparative approach, analyzing the Indonesian landscape against the FIDIC international standards and the Statutory Adjudication models of the United Kingdom and Singapore. The findings elucidate a critical "legal gap" where DB decisions, despite being contractually binding, lack public executorial authority (executorial title). This institutional weakness incentivizes moral hazard, allowing non-compliant parties to evade immediate financial obligations through judicial delays. Consequently, this study proposes a regulatory reconstruction by integrating the principle of temporary finality into the national legislative framework, specifically through the amendment of the Construction Services Law or the Arbitration Law. The proposed model advocates for a "fast-track enforcement" mechanism within the District Courts, predicated on a limited judicial review that precludes the re-examination of technical merits. Such a reform is imperative to safeguard project liquidity (cash flow), ensure legal certainty (rechtszekerheid), and fortify the resilience of National Strategic Projects against systemic disruption.